Pengaruh Sex Rasio dalam Perkawinan Ayam Kokok Balenggek terhadap Fertilitas, Daya Tetas dan Bobot Tetas - Asri, Alfian; Surtina, Dara (Jurnal Peternakan Mahaputra, 2020)
This study aims to determine the effect of sex ratio in mating Kokok Balenggek Chicken (KBC) to fertility,hatchability and hatching weight. The design used was Completely Randomized Design (CRD) with the treatment of sexratio at KBC mating that is : 1: 5, 1: 7, 1: 9 and 1: 11. Each treatment is repeated 4 times and each repeat consist of 5items egg. The variables observed were fertility, hatchability and hatching weight. The results of the diversity analysisshowed that the difference in sex ratio in mating of KBC resulted in an unstable difference (P>0.05) to fertility (85.00 ±10.00%, 75.00 ± 25.17%, 80.00 ± 16.33 %, 65,00 ± 10,00%), hatchability (77,50 ± 16,58%, 66,25 ± 26,89%, 71,25 ±21,75%, 60,42 ± 18,48% ) and hatching weight (29.74 ± 0.44 gr, 30.01 ± 0.82 gr, 29.34 ± 0.28 gr, 30.47 ± 0.51 gr). Itcan be concluded that the sex ratio of 1:11 in the mating of KBC produces fertility, hatchability and hatching weightthat is not different from the sex ratio of 1: 5, 1: 7 and 1: 9. Sex ratio of 1 : 11 can be recommended in KBC mating.